Using suitable identity simplify: (Z²+ 2)(Z²- 3)

Question

Using suitable identity simplify: (Z²+ 2)(Z²- 3)

in progress 0
Sophia 4 weeks 2021-08-17T20:45:25+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-17T20:47:04+00:00

    Answer:

    z {4}  - 3z {}^{2}  + 2z {}^{2}  - 6 \\ z {}^{4}  - z {}^{2}  - 6

    Step-by-step explanation:

    answer is that question by a u abhi

    0
    2021-08-17T20:47:10+00:00

    Hi ,

    ***********************

    We know the algebraic identity ,

    ( a + b + c )² = a²+b²+c²+2ab+2bc+2ca

    *********************************

    Here ,

    a = 2x,

    b = – y ,

    c = z ,

    [ 2x + ( -y ) + z ]²

    = (2x)²+(-y)²+z²+2(2x)(-y)+2(-y)z+2z(2x)

    = 4x² + y² + z² – 4xy – 2yz + 4zx

    I hope this helps you.

    : )

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )